Fournier’s gangrene secondary to marsupialization of Bartholin’s gland: a case report - Ramirez, Luis F.; Moyano, Maria I.; Viteri, Diego F.; Puente, Leonardo A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
We present the case of a 38-year-old patient without risk factors, who presented with Fournier’s gangrene secondary to marsupialization of Bartholin´s gland. Fournier´s gangrene is an extremely rare complication after the instrumented management of Bartholin´s gland abscess. The case aims to explore further evidence regarding the clinical presentation, diagnosis, and timely management of these surgical complication, due to its rapid progression it can compromise the patient´s life.